Key Factors of Enterprise Development: Evidence from Biogas Sector of Nepal - Yadav, Maheshwar Prasad; Pradhan, Radhe S. (Journal of Advanced Academic Research, 2017)
This paper aims at determining key factors for enterprise development in biogas sector in Nepal. The variables are introduced via an extension of the econometric model, which explicitly includes Almon (1965) Polynomial Lag Model using SPSS. The number of biogas companies comprises as a dependent variable for the indicator of enterprise development while number of biogas plants, numbers of biogas plants constructed with loan, micro credit i.e., loan, and subsidy are included as independent variables. The empirical results were estimated using annual data of 22 years from fiscal year 1992/93 to 2013/14 with entire study period divided into different sub-periods. The study reveals that enterprise development is influenced not only by the current values of the key factors but also by the past values. The study also shows that number of biogas plants and subsidy play a very strong role while number of plants constructed with loan and loan play a weak role in enterprise development in the context of biogas sector of Nepal. The paper can be extended by investigating characteristics of renewable energy enterprises and renewable energy entrepreneurs to get a greater insight into the results.